Dose- and time-dependent renoprotection of Angelica sinensis in patients with chronic kidney disease: A longitudinal cohort study - Chen, Hsiao-Tien; Yu, Ben-Hui; Yeh, Ming-Hsien; Hung, Shih-Kai; Chen, Yi-Chun (Frontiers in Pharmacology, 2023)
Background: Based on their anti-oxidative and anti-fibrotic properties, Angelica sinensis (Oliv.) Diels roots [Apiaceae; Radix Angelicae sinensis] (Danggui [abbreviated as S in the context]), Astragalus membranaceus (Fisch.) Bunge [Fabaceae; Astragalus membranaceus] (Huangqi [A]), Rheum palmatum L. [Polygonaceae; Rheum palmatum] (Dahuang [R]), and Salvia miltiorrhiza Bunge [Lamiaceae; Salvia miltiorrhiza Bunge radix et rhizoma] (Danshen [D]) are potential renoprotective Chinese herbal medicines (CHMs). Renoprotection using ARD alone for the treatment of chronic kidney disease (CKD) has been documented in pre-clinical, clinical, and meta-analysis research; however, only pre-clinical data is available for the use of S alone. Moreover, with an increasing number of CKD patients taking prescribed CHMs, hyperkalemia risk remains unclear. Methods: This study retrospectively analyzed national health insurance claims data in 2001-2017. Propensity score matching was used to analyze renal and survival outcomes and the dose-response effects of S without ARD use in 18348 new S users, 9174 new ARD users, and 36696 nonusers. Cox proportional hazard regression was used to investigate adjusted hazard ratios (aHRs) for end-stage renal disease (ESRD) in the presence of competing mortality and death. The additive effect of S herb in single to compounds was also analyzed. Additionally, to analyze hyperkalemia risk, an exact match on each covariate was used to include 42265 new CHM users and nonusers, while Poisson regression was used to estimate adjusted incidence rate ratio (aIRR) of hyperkalemia of prescribed CHMs. Results: S users and ARD users were associated with aHRs of 0.77 (95% confidence interval, 0.69-0.86) and 1.04 (0.91-1.19), respectively, for ESRD and 0.55 (0.53-0.57) and 0.71 (0.67-0.75), respectively, for death. The renal and survival benefits of S use were consistent on several sensitivity analyses. The dose- and time-dependent renoprotection and dose-dependent survival benefit were observed for S use. The top two additive renoprotective collocations of S herb in compounds were Xue-fu-zhu-yu-tang and Shen-tong-zhu-yu-tang, followed by Shu-jing-huo-xue-tang and Shen-tong-zhu-yu-tang. Moreover, CHM users were associated with aIRR of 0.34 (0.31-0.37) for hyperkalemia. Conclusions: This study suggests a dose- and time-dependent renoprotection and dose-dependent survival benefit of S herb in compounds and no increased hyperkalemia risk of prescribed CHMs in CKD patients.